Chapter Nanostructured Pure and Doped Zirconia: Synthesis and Sintering for SOFC and Optical Applications - Lu, Yiying; Balima, Félix; Valsan, Sorina; Robert Piticescu, Radu; Prakasam, Mythili; Largeteau, Alain (InTechOpen, 2018)
Zirconia is a multifunctional material with potential applications in wide domains. Rare-earth doped zirconia and stabilized zirconia yield interesting properties based on the phase transitions induced by the sintering conditions. Zirconia nanopowders were prepared by hydrothermal technique. Synthesis methods of zirconia with various rare earths are discussed here. An overview of the sintering of zirconia-based ceramics is presented in particular for SOFC and sensors and optical applications.
English
Keywords: Engineering: general; sintering, solid oxide fuel cell, optical ceramics, hydrothermal synthesis